Factors associated with time to breast cancer diagnosis and treatment in unscreened women in Portugal. Issue 6 (3rd July 2019) - Nouws, Sónia; Brandão, Mariana; Fontes, Filipa; Pereira, Susana; Dias, Teresa; Ribeiro, Ana Isabel; Lunet, Nuno; Peleteiro, Bárbara
ABSTRACT: Delays in detection, diagnosis and treatment may lead to poorer prognosis in women with breast cancer. We quantified time intervals from first detection (FD) to diagnosis (D) and first treatment (FT) and identified associated factors. We studied 282 patients diagnosed with breast cancer during 2012 at the Breast Clinic of the Portuguese Institute of Oncology in Porto, Portugal using face-to-face interview and medical records. Associations of sociodemographic and clinical characteristics with time intervals was computed using adjusted percentage differences (adjPD) after logarithmic transformation, odds ratios (adjOR) for comparing the highest and lowest thirds of the distribution and 95 percent confidence intervals (CI) for both measures, using linear and logistic regression, respectively. The median times between FD and D and FT were 31 and 44 days, respectively. Significantly longer periods between FD and D were found in symptomatic women (adjPD = 99.5, 95 percent CI: 37.1, 190.0; adjOR = 3.16, 95 percent CI: 1.57, 6.33). More advanced stage was associated with shorter intervals between D and FT (adjPD = −33.8, 95 percent CI: −44.2, −21.5; adjOR = 0.14, 95 percent CI: 0.05, 0.34). Although some differences according to clinical characteristics were observed, they did not seem to translate into inequities in access to public healthcare in this group of women.